Tingkat Stres Narapidana Ditinjau dari Vonis Hukuman: Penelitian - Hapsari Nina Nabilah; Hasnida; Rahma Fauzia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the stress levels of prisoners based on their sentence type, namely sentences of more than one year (BI), life imprisonment, and death penalty. This research employed a descriptive quantitative approach involving 337 male inmates from Correctional Institution X, consisting of 298 inmates with sentences of more than one year (BI), 33 with life imprisonment, and 6 with death sentences. The instrument used was the Perceived Stress Scale (PSS), which had been adapted into Indonesian, and the data were analyzed using descriptive statistics.The results showed that inmates serving life sentences had the highest average stress score (M = 22.06), followed by those sentenced to death (M = 21.80), and the lowest was found among inmates with fixed-term sentences (M = 20.65). Although the differences in mean scores were not substantial, the distribution of categories indicated that inmates with heavier sentences tended to fall into higher stress categories. Sentence duration appeared to be a situational factor influencing inmates’ stress levels, particularly among those serving long and indefinite sentences such as life imprisonment and death penalty. The study recommended the provision of more intensive psychological services to help inmates manage emotional distress during their incarceration.